Simultaneous detection of small molecule thiols with a simple 19F NMR platform. Issue 3 (24th November 2020) - Chai, Zhaofei; Wu, Qiong; Cheng, Kai; Liu, Xiaoli; Jiang, Ling; Liu, Maili; Li, Conggang
Abstract : A 19 F NMR platform, capable of discriminating various small molecule thiols, was designed for in-cell thiol differentiation and monitoring, and further detection of the γ-GT activity, demonstrating the wide applications in thiol-related processes. Abstract : Thiols play critical roles in regulating biological functions and have wide applications in pharmaceutical and biomedical industries. However, we still lack a general approach for the simultaneous detection of various thiols, especially in complex systems. Herein, we establish a 19 F NMR platform where thiols are selectively fused into a novelly designed fluorinated receptor that has two sets of environmentally different 19 F atoms with fast kinetics ( k 2 = 0.73 mM −1 min −1 ), allowing us to generate unique two-dimensional codes for about 20 thiols. We demonstrate the feasibility of the approach by reliably quantifying thiol drug content in tablets, discriminating thiols in living cells, and for the first time monitoring the thiol related metabolism pathway at the atomic level. Moreover, the method can be easily extended to detect the activity of thiol related enzymes such as γ-glutamyl transpeptidase. We envision that the versatile platform will be a useful tool for detecting thiols and elucidating thiol-related processes in complex systems.